2018
DOI: 10.2478/intox-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the time-dependent dermatotoxicity of mechlorethamine using the mouse ear vesicant model

Abstract: Mechlorethamine (HN2) is an alkylating agent and sulfur mustard gas mimetic which is also used in anticancer therapy. HN2 is associated with skin inflammation and blistering which can lead to secondary infections. The purpose of the present study was to investigate the time-dependent dermatotoxicity of HN2 using the mouse ear vesicant model (MEVM). To this end, our operational definition of dermatotoxicity included tissue responses to HN2 consistent with an increase in the wet weights of mouse ear punch biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…At least one of the cutaneous responses to HN2 observed in mouse skin involves increased tissue expression of MMP-9, a matrix metalloproteinase that directly degrades extracellular matrix (ECM) proteins and activates cytokines and chemokines to regulate tissue remodeling in response to chemical injury. Our lab ( Cuffari et al, 2018 , Tumu et al, 2020 ) and others ( Kumar et al, 2015 , Wormser et al, 2002 ) have found that HN2 increases the expression of MMP-9 in mouse skin. In addition, we ( Tumu et al, 2020 ) and others ( Biyashev et al, 2020 , Composto et al, 2016 , Kumar et al, 2015 ) have observed that HN2 increases the tissue expression of inducible nitric oxide synthase (iNOS) in mouse skin, which, in turn, is important for generating cytotoxic levels of nitric oxide in the skin ( Composto et al, 2016 , Nguyen and Soulika, 2019 ).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…At least one of the cutaneous responses to HN2 observed in mouse skin involves increased tissue expression of MMP-9, a matrix metalloproteinase that directly degrades extracellular matrix (ECM) proteins and activates cytokines and chemokines to regulate tissue remodeling in response to chemical injury. Our lab ( Cuffari et al, 2018 , Tumu et al, 2020 ) and others ( Kumar et al, 2015 , Wormser et al, 2002 ) have found that HN2 increases the expression of MMP-9 in mouse skin. In addition, we ( Tumu et al, 2020 ) and others ( Biyashev et al, 2020 , Composto et al, 2016 , Kumar et al, 2015 ) have observed that HN2 increases the tissue expression of inducible nitric oxide synthase (iNOS) in mouse skin, which, in turn, is important for generating cytotoxic levels of nitric oxide in the skin ( Composto et al, 2016 , Nguyen and Soulika, 2019 ).…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, we used the MEVM to investigate cutaneous responses to HN2. We observed and confirmed that 24 hr after a single topical application of HN2, mouse ear skin exhibited massive immune cell infiltration, necrosis, increased TUNEL activity (an indicator of DNA injury), an upregulation of the tissue injury-associated matrix metalloproteinase 9 (MMP-9) ( Cuffari et al, 2018 , Kumar et al, 2015 , Tumu et al, 2020 , Wormser et al, 2002 ) and an increased tissue presence of the proinflammatory enzyme inducible nitric oxide synthase (iNOS) ( Biyashev et al, 2020 , Composto et al, 2016 , Kumar et al, 2015 , Tumu et al, 2020 ). MMP-9 is a proteolytic enzyme capable of degrading extracellular matrix proteins such as denatured collagen (gelatin) and collagen types IV, V, VII, IX and X ( van der Jagt et al, 2006 ).…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations